The construction of drawings and movies : models for architectural design and analysis - Forget, Thomas (New York : Routledge, 2013)
'Here, clearly demonstrated, are principles for constructing linear perspective drawings and experimental works of cinema that will help you use digital tools in the design studio. As an architect, your drawings need to examine how parts or spaces connect and relate in abstract, or analytical ways. These approaches to drawing and modeling will let you see the information that analytical graphics show. And you'll learn to use film in the same way. Author Thomas Forget explains how to construct linear perspective drawings and illustrates experimental movie-making strategies. By combining these two methods you can analyze and improve your drawings and increase your graphic literacy. He includes case studies of recent drawing, movie-making, and architecture created by practicing architects, such as Mies van der Rohe and Lewis Tsurumaki Lewis; by filmmakers, such as William Whyte and Thom Andersen; and by students, to show you the best of what's been done. And he presents the theory behind how to represent buildings that will inspire and get you thinking'--
Introduction: Analytical & Pictorial Imagery -- Logics of Construction. The Demystification of Linear Perspective -- The Making of a Movie -- Matters of History. The Non-linear Progression of Linear Perspective -- The Extents and Limits of Architecture-Cinema -- Indeterminate Projections. Architectural Drawings -- Architectural Movies -- Epilogue: The Reflexivity of Architecture and Projection.
Includes bibliographical references and index.
Keywords: Perspective; Architectural drawing -- Technique; Architectural drawing -- Data processing; Experimental films -- Production and direction